Next level screenwriting : insights, ideas and inspiration for the intermediate screenwriter - Landau, David, 1956-; Carren, David Bennett (London ; New York : Routledge, Taylor & Francis Group, 2019)
"Next Level Screenwriting is an intermediate screenwriting book, for those that have already learned the basics of screenwriting, written a screenplay or two already and want to bring their writing and stories to the next level. Each chapter of the book examines a specific aspect of screenwriting, such as character, dialogue and theme, and then provides the reader with ideas, tips and inspiration to apply to their own writing. Rather than being another "how to" book, this book features a variety of case studies and challenging exercises throughout--derived from a broad selection of successful feature films and TV shows from the 1940s to present day--to help spark the imagination of the writer as they work through different styles and approaches of screenwriting. An absolute must-read for any screenwriter wanting to improve their writing and storytelling skills"--
Don't be afraid of genre: keeping your promise to your viewer -- The write approach: finding how to approach telling your story and the -- Point of attach -- Character depth - thinking about more layered characters and their motivations -- Dialogue that does more than further the plot -- Poetic description- writing your settings can be as creative as writing your story -- Finding the theme: discovering what your writing is all about -- Chapter 7; first person narrative screenwriting - writing voice over narration and found footage stories -- Dealing with multiple protagonist syndrome or navigating the ensemble screenplay -- Based on true events & research: writing the core of the truth without being boring -- Set-up, pay-off and the twist: writing in things that go around and came around -- Writing for a budget - writing screenplays under budget constraints -- Rewriting: the pain and the gain -- Wrote the script, now what?.
"A Focal Press Book"--Cover.
Includes bibliographical references and index.
Keywords: Motion picture authorship